1996
DOI: 10.1029/96rs00088
|View full text |Cite
|
Sign up to set email alerts
|

An ambiguity‐function‐based method for analysis of Doppler decompressed radar signals applied to EISCAT measurements of oblique UHF‐VHF meteor echoes

Abstract: Binary phase modulation using Barker codes as the modulating sequences is often used as a pulse compression technique in incoherent scatter radar measurements of the ionospheric E region. Demodulation of the compressed signal is usually accomplished by matched filtering techniques. If the target has appreciable velocity, the resulting Doppler shift detunes the scattered signal relative to the filter, and the target response spreads over a large range interval. The paper describes the development of a new data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 11 publications
5
61
0
Order By: Relevance
“…However, as the Doppler shift increases, less and less of the signal power eventually falls within the ®lter. This e ect is described in detail in the Appendix of Wannberg et al (1996), and shown in their Fig. A2.…”
Section: The Velocity Estimate Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, as the Doppler shift increases, less and less of the signal power eventually falls within the ®lter. This e ect is described in detail in the Appendix of Wannberg et al (1996), and shown in their Fig. A2.…”
Section: The Velocity Estimate Methodsmentioning
confidence: 99%
“…There are always spread over 25 gates, and they can by no means represent any physical ionization distributions in the ionosphere. In Wannberg et al (1996) we have shown that the forms are consequences of the Barker-coding of the radar pulses. The ambiguity function of the used 13 baud Barker code spreads over 2´13 A 1 = 25 gates.…”
Section: The Velocity Estimate Methodsmentioning
confidence: 99%
See 3 more Smart Citations